Kekerasan Dalam Rumah Tangga Dalam Perspektif Hukum Islam dan Hukum Publik - E, Ekawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study explores domestic violence (DV) from the perspective of Islamic law and public law in Indonesia using a normative juridical approach. Data were collected through documentation of Qur’anic verses, hadith interpretations, classical and contemporary fiqh books, and Law No. 23 of 2004 concerning the Elimination of Domestic Violence. Domestic violence has wide-ranging impacts, including physical injury, psychological trauma, and social disintegration, threatening family harmony and public order. The findings show that Islamic law strictly prohibits all forms of DV as jarimah that contradict the objectives of Sharia (maqāṣid al-syarī‘ah), which emphasize justice, compassion, and protection of human dignity. In contrast, public law treats DV as a criminal act subject to penal sanctions while providing legal protection and recovery for victims. Integrating Islamic moral values with public law enforcement mechanisms is essential to eradicate DV and build safe, harmonious families.